2003
DOI: 10.1046/j.1365-2036.2003.t01-1-01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Triple vs. quadruple therapy for treating Helicobacter pylori infection: an updated meta‐analysis

Abstract: Triple vs. quadruple therapy for treating Helicobacter pylori infection: an updated meta-analysis Sirs, Since we submitted our paper, ÔTriple vs. quadruple therapy for treating Helicobacter pylori infection: a meta-analysisÕ, for publication in Alimentary Pharmacology and Therapeutics, 1 a new study comparing triple with quadruple therapy has been published. 2 Full-text reports of two of the studies included in the metaanalysis in abstract form have also been published. 3, 4The objective of this letter is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 40 publications
6
70
0
4
Order By: Relevance
“…8 Furthermore, triple and quadruple therapies seem to be also roughly equivalent in terms of effectiveness when administered as first-line treatment. 17 Subsequent second-line therapy should use quadruple therapy with a PPI, bismuth, metronidazole and tetracycline, but a recent review on rescue regimens reported as the weighted eradication mean with this rescue treatment was of 77.2% 18 Therefore, it remains a therapeutic dilemma which treatments using in those 20-30% of patients still infected after two eradication courses. In this scenario, the utility of the culture (with consequent antibiotic-susceptibility testing) and the moment when it must be performed after eradication failure are both controversial.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, triple and quadruple therapies seem to be also roughly equivalent in terms of effectiveness when administered as first-line treatment. 17 Subsequent second-line therapy should use quadruple therapy with a PPI, bismuth, metronidazole and tetracycline, but a recent review on rescue regimens reported as the weighted eradication mean with this rescue treatment was of 77.2% 18 Therefore, it remains a therapeutic dilemma which treatments using in those 20-30% of patients still infected after two eradication courses. In this scenario, the utility of the culture (with consequent antibiotic-susceptibility testing) and the moment when it must be performed after eradication failure are both controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have compared the efficacy of triple versus quadruple therapy, and a recent meta-analysis has assessed these studies [10] . Eradication rates were not significantly different among patients receiving triple or quadruple therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Triple therapy given for a 10-d period achieved an intention-totreat eradication rate of 79% compared with 77% for a 7-d period. Quadruple therapy on the other hand gave an intention-to-treat eradication rate of 83% for a 10-d period and 80% for a 7-d period [10] . The eradication rates by intention-to-treat analysis among patients receiving either triple or quadruple therapy in this study were almost similar to those obtained previously [4,10,11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Studies have shown that the eradication rates with both of these regimens range from 70 % to 85 %. [60][61][62][63] Case Continued. The patient sees you in follow-up, at which time you decide to confirm eradication with a fecal antigen test, which comes back positive.…”
Section: What Should Be Used For Primary Therapy?mentioning
confidence: 99%